A Phylogeographic Analysis of Porcine Parvovirus 1 in Africa - Giovanni Franzo; Habibata Lamouni Zerbo; Bruno Lalidia Ouoba; Adama Drabo Dji-Tombo; Marietou Guitti Kindo; Rasablaga Sawadogo; Jelly Chang’a; Stella Bitanyi; Aloyce Kamigwe; Charles Mayenga; Modou Moustapha Lo; Mbengué Ndiaye; et al. (Viruses, 2023)
Porcine parvovirus 1 (PPV1) is recognized as a major cause of reproductive failure in pigs, leading to several clinical outcomes globally known as SMEDI. Despite being known since the late 1960s its circulation is still of relevance to swine producers. Additionally, the emergence of variants such as the virulent 27a strain, for which lower protection induced by vaccines has been demonstrated, is of increasing concern. Even though constant monitoring of PPV1 using molecular epidemiological approaches is of pivotal importance, viral sequence data are scarce especially in low-income countries. To fill this gap, a collection of 71 partial VP2 sequences originating from eight African countries (Burkina Faso, Côte d’Ivoire, Kenya, Mozambique, Namibia, Nigeria, Senegal, and Tanzania) during the period 2011–2021 were analyzed within the context of global PPV1 variability. The observed pattern largely reflected what has been observed in high-income regions, i.e., 27a-like strains were more frequently detected than less virulent NADL-8-like strains. A phylogeographic analysis supported this observation, highlighting that the African scenario has been largely shaped by multiple PPV1 importation events from other continents, especially Europe and Asia. The existence of such an international movement coupled with the circulation of potential vaccine-escape variants requires the careful evaluation of the control strategies to prevent new strain introduction and persistence.